Fracture toughness characterization of thin Ti/SiC composites - Ma, Wei (Cranfield University, 2011)
Titanium based alloys reinforced uniaxially with silicon carbide fibres (Ti/SiC) are advanced and innovative materials for aerospace vehicles. To avoid potential problems, these new materials should be extensively tested and analyzed before application. This research focuses on experimental fracture toughness study on 0.5 mm thick Ti/SiC composite materials for aerospace applications. The fracture toughness tests are mainly based on BS 7448 with some modifications for transversely isotropic behaviour of the composite materials. By loading on specimens in the direction perpendicular to the fibre axis, three critical values of fracture toughness parameters characterizing fracture resistance of material, plane strain fracture toughness [Plane strain fracture toughness }, critical crack tip opening displacement [Critical crack tip opening displacement ] and critical J-integral [Critical at the onset of brittle crack extension or pop-in when Δa is less than 0.2 mm. ]are measured for two kinds of titanium alloy specimens and three kinds of Ti/SiC composites specimens. The values of [Provisional value of Plane strain fracture toughness ] obtained from the fracture toughness tests are not valid [Plane strain fracture toughness ] for these materials, since the thickness of specimens is insufficient to satisfy the minimum thickness criterion; however, the results could be used as particular critical fracture toughness parameter for 0.5 mm thick structures of the materials. The valid values of [Critical J at the onset of brittle crack extension or pop-in when Δa is less than 0.2 mm. ] and [Critical crack tip opening displacement ] could be used as fracture toughness parameters for all thickness of structures of the materials. The results also show that: fracture toughness of the titanium alloys decreases dramatically after being unidirectional reinforced with SiC fibre, which is mainly triggered by poor fibre/matrix bonding condition. Moreover, Ti-Al3-V2.5 reinforced with 25% volume fraction SiC fibre performs better than the other two composites in fracture resistance.
Keywords: Ti/SiC composites; facture toughness; tests; fibre direction perpendicular to the loading direction; 0.5 mm thick